Rapid and Effective Recovery of Oleanolic and Maslinic Acids from Olive Leaves Using SFE and pH-Zone Centrifugal Partition Chromatography - Lemonia Antoniadi; Apostolis Angelis; Theodora Nikou; Dimitris Michailidis; Leandros A. Skaltsounis (Molecules)
Olive leaves, the main byproducts of olive cultivation, are characterized by a plethora of bioactive metabolites with significant nutritional value. Their main pentacyclic triterpenes, Oleanolic Acid (OA) and Maslinic Acid (MA), are two high added-value compounds with remarkable activities. This study aimed to develop an efficient methodology for extracting and purifying OA and MA, utilizing Supercritical Fluid Extraction (SFE) and Centrifugal Partition Chromatography (CPC)—two modern, scalable, and green techniques. A total of 21 g of olive leaves were subjected to SFE using supercritical CO2 and ethanol as co-solvent. The extraction employed a step gradient mode, starting with 100% CO2 and incrementally increasing ethanol (0–10% w/w) every 20 min. Fractions rich in OA and MA (500 mg) were further purified via CPC, utilizing pH zone refining to exploit the protonation and deprotonation properties of acidic triterpenes. The biphasic solvent system consisted of n-hexane, ethyl acetate, ethanol, and water (8:2:5:5 v/v/v/v), with trifluoroacetic acid added to the stationary phase and triethylamine added to the mobile phase. This two-step process yielded 89.5 mg of OA and 28.5 mg of MA with over 95% purity, as confirmed by HPLC-ELSD and 1H-NMR. Moreover, purified compounds and SFE fractions exhibited promising elastase and collagenase inhibition, highlighting them as dermocosmetic agents.